Pengaruh FOMO dan E-WOM terhadap Pembelian Impulsif Produk The Originote di Shopee (Studi pada Gen-Z Kota Bandung) - Khaida Rahayu Oktora; Nur Hayati (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2026)
The tendency for impulse buying in Indonesia’s beauty sector is rising, prompting this study to explore the effects of Fear of Missing Out (FoMO) and Electronic Word of Mouth (E-WOM) on impulsive purchases of The Originote products on Shopee among Gen-Z in Bandung. Using a quantitative method, 135 Gen-Z participants aged 18-28, active Shopee users who had bought The Originote products, were surveyed through questionnaires distributed in strategic locations in Bandung. Data analysis using multiple linear regression via SPSS revealed that FoMO significantly influences impulsive buying, with a score of 11.420 and significance <0.001. In contrast, E-WOM showed no significant partial effect, with a score of -0.147 and significance 0.883 (>0.05). However, combined FoMO and E-WOM factors significantly affected impulsive buying (F = 81.405, p < 0.001) with an R² of 0.552, indicating these variables explain 55.2% of impulsive buying behavior, while other factors contribute to the rest.